MISKONSEPSI PENYELESAIAN SENGKETA JAMINAN FIDUSIA DALAM PRAKTIK LEASING OLEH BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) - Ruli Agustin (Jurnal Hukum Statuta, 2024)
The Consumer Dispute Settlement Agency (BPSK) in Indonesia has been a primary pillar in ensuring consumer protection since its establishment based on Law Number 8 of 1999 concerning Consumer Protection. Dispute resolution, particularly those related to fiduciary guarantees in leasing practices, has been a major focus in the realm of consumer law. The conflict of jurisdiction between BPSK and the District Court in resolving leasing disputes has led to misconceptions about the role and authority of BPSK in resolving leasing disputes. Based on this axiom, the author conducted this research to identify and analyze misconceptions present in leasing dispute practices in Indonesia. The research method employed was normative law with a legislative approach and case studies. The research findings affirm that although the Consumer Dispute Settlement Agency (BPSK) has authority in resolving consumer disputes, it lacks jurisdiction in leasing dispute resolution, thus necessitating a more detailed approach to provide a comprehensive understanding of the role and authority of BPSK to ensure complete consumer protection.